Pattern recognition receptor CD14 gene polymorphisms in alcohol use disorder patients and its Influence on liver disease susceptibility - Roy, Neelanjana; Nadda, Neeti; Kumar, Hem; Prasad, Chandreswar; Kumar Jha, Jyotish; Pandey, Hem Chandra; Vanamail, Perumal; Saraya, Anoop; Balhara, Yatan Pal Singh; Shalimar; Nayak, Baibaswata (Frontiers in Immunology, 2022)
Background Alcohol use disorders (AUDs) leading to liver disease is major concern over other spectrum of disorder. Excessive alcohol consumption resulting in leaky gut syndrome is attributed to alcohol-induced liver injury through portal translocation of bacterial endotoxin. Susceptibility to alcoholic liver disease (ALD) in AUD patients could be dependent upon genes responsible for inflammation and alcohol metabolism. The pattern recognition receptor CD14 gene is a major player in endotoxin-mediated inflammation and susceptibility to ALD. This study investigated the genetic association of CD14 polymorphisms and other mechanisms relevant to altered inflammatory responses leading to ALD. Methods Patients with alcohol use disorder with ALD (n = 128) and without liver disease (ALC, n = 184) and controls without alcohol use disorder (NALC, n = 152) from North India were enrolled. The CD4 gene polymorphisms in the North Indian population were evaluated by RFLP and sequencing. Secretory CD14 (sCD14), LBP, TLR4, MD2, TNFα, IL1b, IFNγ, IL6, IL10, and IL4 levels in serum were measured by ELISA among groups. The influence of polymorphisms on CD14 gene promoter activity and circulatory bacterial DNA level was determined. Results The CD14 gene promoter and exonic region SNPs were found to be monomorphic, except for SNP rs2569190 for the North Indian population. The genetic association of SNP rs2569190(C/T) with the risk of developing ALD was found significant for TT genotype [ORTT, 95% CI = 2.19, 1.16–4.13 for ALD vs. ALC and OR, 2.09, 1.18–3.72 for ALD vs. NALC]. An increased sCD14 level was observed in AUD patients compared to NALC control. Increased levels of LBP, TLR4, TNFα, IL1β, IFNγ, and IL6 and reduced levels of MD2, IL10, and IL4 were observed among the ALD patients compared to the other two control groups. Elevated levels of pro-inflammatory and reduced levels of anti-inflammatory cytokines were observed in the risk genotype TT groups of ALD patients and the ALC group compared to NALC. Promoter activity was observed in the intronic region flanking SNPs and risk genotype can influence reporter activity, indicating CD14 gene expression. Conclusion Enhanced CD14 expression associated with inflammatory responses increases susceptibility to ALD in the TT genotype of AUD patients.